1999
DOI: 10.1063/1.1149679
|View full text |Cite
|
Sign up to set email alerts
|

Thermal noise in a high Q cryogenic resonator

Abstract: In order to evaluate the feasibility of a mixed mechanical and electrical multimode matching network for a resonant gravitational wave detector, current noise measurements were performed on a high quality factor LC resonator, based on a superconducting coil, by using a dc SQUID weakly coupled to the coil. We present a method to identify different noise sources in the system by their dependence on the temperature or on the resonator quality factor. Measurements performed at quality factors up to 10 6 in the tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 15 publications
1
15
0
Order By: Relevance
“…Different behaviors are instead observed by changing the capacitor. In particular, the capacitors used by Bonaldi et al 3 lead to a quality factor nearly independent of temperature, as was reported. Given these results, in the near future we plan to use homemade vacuum-gap capacitors, which should both improve the quality factor, because of reduced dielectric losses, 17 and give further indication on the origin of the temperature dependent dissipation.…”
Section: Resultsmentioning
confidence: 52%
See 3 more Smart Citations
“…Different behaviors are instead observed by changing the capacitor. In particular, the capacitors used by Bonaldi et al 3 lead to a quality factor nearly independent of temperature, as was reported. Given these results, in the near future we plan to use homemade vacuum-gap capacitors, which should both improve the quality factor, because of reduced dielectric losses, 17 and give further indication on the origin of the temperature dependent dissipation.…”
Section: Resultsmentioning
confidence: 52%
“…Regarding the quality factor of the resonator, we have observed a rather unexpected dependance on temperature. Figure 4 shows the measured dissipation expressed by 1 / Q as function of the inverse of temperature 1 / T. The evident increase of 1 / Q at low temperature points to some kind of dissipation which grows roughly as 1 / T. In order to understand the origin of this unexpected behavior, which has not been pointed out in a previous work, 3 we have performed further quality factor measurements with a different resona- tor setup. For this purpose the resonator has been housed in the same experimental probe described by Bonaldi et al, 3 which allows quicker tests with less liquid helium consumption in the temperature range 1.3-4.2 K. We have found that the temperature dependent dissipation is still present, and does not change significantly by using different coils with the same inductance or placing in parallel to the resonator an additional ϳ200 pF formvar capacitance to simulate an increased coil stray capacitance.…”
Section: Resultsmentioning
confidence: 82%
See 2 more Smart Citations
“…2 shows the projected reach of the planned DM Radio experiment, which is optimized to detect small magnetic fields and is expected to consist of a meter 3 detector with T LC ¼ 10 mK and Q ¼ 10 6 , assuming that it is modified to include a meter 3 upstream PHYSICAL REVIEW LETTERS 124, 011801 (2020) 011801-4 deflector. The construction of thermal-noise-limited resonant LC circuits operating at kHz frequencies with quality factors of Q ≃ 10 6 has already been firmly established by the existing gravity-wave experiment, AURIGA [39][40][41]. Therefore, we also consider a future dedicated experimental configuration optimized for measuring the electric field signal, as shown by the lines labeled "E field (I-III)" in Fig.…”
mentioning
confidence: 99%